2022 Systematic Review of Evidence-Based Guidelines for Prehospital Care. (17th February 2023) - Martin-Gill, Christian; Brown, Kathleen M.; Cash, Rebecca E.; Haupt, Rachel M.; Potts, Benjamin T.; Richards, Christopher T.; Patterson, P. Daniel; ,
Abstract: Introduction: Multiple national organizations and federal agencies have promoted the development, implementation, and evaluation of evidence-based guidelines (EBGs) for prehospital care. Previous efforts have identified opportunities to improve the quality of prehospital guidelines and highlighted the value of high-quality EBGs to inform initial certification and continued competency activities for EMS personnel. Objectives: We aimed to perform a systematic review of prehospital guidelines published from January 2018 to April 2021, evaluate guideline quality, and identify top-scoring guidelines to facilitate dissemination and educational activities for EMS personnel. Methods: We searched the literature in Ovid Medline and EMBASE from January 2018 to April 2021, excluding guidelines identified in a prior systematic review. Publications were retained if they were relevant to prehospital care, based on organized reviews of the literature, and focused on providing recommendations for clinical care or operations. Included guidelines were appraised to identify if they met the National Academy of Medicine (NAM) criteria for high-quality guidelines and scored across the six domains of the Appraisal of Guidelines for Research and Evaluation (AGREE) II tool. Results: We identified 75 guidelines addressing a variety of clinical and operational aspects of EMS medicine. About half (n = 39, 52%) addressed time/life-critical conditions and 33 (44%) contained recommendations relevant to non-clinical/operational topics. Fewer than half (n = 35, 47%) were based on systematic reviews of the literature. Nearly one-third (n = 24, 32%) met all NAM criteria for clinical practice guidelines. Only 27 (38%) guidelines scored an average of >75% across AGREE II domains, with content relevant to guideline implementation most commonly missing. Conclusions: This interval systematic review of prehospital EBGs identified many new guidelines relevant to prehospital care; more than all guidelines reported in a prior systematic review. Our review reveals important gaps in the quality of guideline development and the content in their publications, evidenced by the low proportion of guidelines meeting NAM criteria and the scores across AGREE II domains. Efforts to increase guideline dissemination, implementation, and related education may be best focused around the highest quality guidelines identified in this review.